THE SCHIZOPHRENIA OF JACK TORRANCE’S CHARACTER PORTRAYED IN“THE SHINING” MOVIE BY STANLEY KUBRICK - Yusfa, Weldina; Nur, Sahril; Abdullah, Abdullah (ELITERATE : Journal of English Linguistics and Literature Studies, 2021)
The Shining is a movie directed by Stanley Kubrick in 1980 with duration 2 hours 26 minutes. The story presented Jack Torrance as a man who dislikes authority. He moved to an isolated hotel with his wife and his son in Colorado over the winter, hoping to improve and cure his poor writing. As the days passed, he began showed the symptoms of schizophrenia and attempt to kill his family. This research aims to analyze the symptoms, the kinds, and the impacts of schizophrenia of the main character (Jack Torrance) in “The Shining” movie using psychological approach based on the theory of Kraepelin and American Psychiatric Association. The researcher analyzed the data using descriptive qualitative method and the result of this research showed that the Jack Torrance experienced positive symptoms, negative symptoms, and cognitive symptoms. But the most dominant symptoms were positive symptoms since he had experienced many hallucinations and delusions. There are several types of schizophrenia experienced by Jack Torrance, including schizophrenic simplex, schizophrenic hebephrenic, schizophrenic catatonic and schizophrenic paranoid. Moreover, the most dominant types of schizophrenia that Jack Torrance experienced is paranoid schizophrenia since he showed so many hallucinations, emotional, and serious expression in the movie. Lastly, the impacts of schizophrenia experienced by Jack Torrance are ignoring family, relationship conflicts, familial conflicts, and inability to work.